Does Diffusion Restriction Pattern on MRI Predict Stroke Etiology in a Cancer Patient? - Kolukisa, Mehmet; Koyuncu, Bahar A.; Bayrakoglu, Alisan; Asil, Talip (Current Medical Imaging, 2023)
Background: Stroke and cancer are two of the most common health problems. Moreover, stroke is more common in patients with cancer than in the normal population, due to coagulation problems. Knowing the etiology of stroke is important for determining treatment options. This study aimed to determine the relationship between ischemic lesion topographies using diffusion-weighted magnetic resonance imaging (MRI) and the etiology of stroke in patients with cancer. Patients and Methods: All patients with ischemic stroke in the Bezmialem Stroke Registry over a 4- year period were retrospectively analyzed in this study. Patients with acute ischemic stroke and additional diagnoses of solid and active malignancy (excluding hematologic malignancies) were included in the analysis. We investigated whether there was a relationship between the etiology of patients with cancer-related stroke according to the stroke etiologic classification and the diffusion restriction patterns on MRI. Results: In this registry, 32 of 1472 patients were diagnosed as having active cancer. Fourteen patients were evaluated as having definite cardioembolism, eight patients as probable cardioembolism, and four patients had inadequate examinations. Only one patient was classified as having an atherothrombotic stroke. Isolated acute infarction was seen in 15 of 32 patients. In patients with multiple acute infarct areas (n=17), acute lesions characterized by micro embolisms in a single vessel area were detected in four patients, and acute lesions characterized by bilateral (anterior and/or posterior system) micro embolisms in more than one vessel area in 13 patients. Conclusion: The most common etiology of stroke in patients with cancer was found to be embolic/ cardioembolic. This is important for the treatment plans for ischemic stroke in patients with cancer.
Keywords: cancer